Morphology-tuned Pt3Ge accelerates water dissociation to industrial-standard hydrogen production over a wide pH range - Mondal, Soumi; Sarkar, Shreya; Bagchi, Debabrata; Das, Tisita; Das, Risov; Singh, Ashutosh Kumar; Prasanna, Ponnappa Kechanda; Vinod, C. P.; Chakraborty, Sudip; Peter, Sebastian C. (Advanced Materials, 2022)
The discovery of novel materials for industrial-standard hydrogen production is the present need considering the global energy infrastructure. A novel electrocatalyst, Pt3Ge, which is engineered with a desired crystallographic facet (202), accelerates hydrogen production by water electrolysis, and records industrially desired operational stability compared to the commercial catalyst platinum is introduced. Pt3Ge-(202) exhibits low overpotential of 21.7 mV (24.6 mV for Pt/C) and 92 mV for 10 and 200 mA cm(-2) current density, respectively in 0.5 m H2SO4. It also exhibits remarkable stability of 15 000 accelerated degradation tests cycles (5000 for Pt/C) and exceptional durability of 500 h (@10 mA cm(-2)) in acidic media. Pt3Ge-(202) also displays low overpotential of 96 mV for 10 mA cm(-2) current density in the alkaline medium, rationalizing its hydrogen production ability over a wide pH range required commercial operations. Long-term durability (>75 h in alkaline media) with the industrial level current density (>500 mA cm(-2)) has been demonstrated by utilizing the electrochemical flow reactor. The driving force behind this stupendous performance of Pt3Ge-(202) has been envisaged by mapping the reaction mechanism, active sites, and charge-transfer kinetics via controlled electrochemical experiments, ex situ X-ray photoelectron spectroscopy, in situ infrared spectroscopy, and in situ X-ray absorption spectroscopy further corroborated by first principles calculations.
Keywords: Electrochemistry; hydrogen production; intermetallics; water electrolysis

Metal deficiency tailored by the 18-electron rule stabilizes metal-based inorganic compounds - Singh, Ashutosh Kumar; Mumbaraddi, Dundappa; Mishra, Vidyanshu; Roy, Soumyabrata; Vinod, C. P.; Peter, Sebastian C. (Chemistry of Materials, 2023)
The 18-electron (18-e(-)) rule is typicallyrestrictedto predicting the stability of transition-metal-based complexes. Herein,we report the use of the 18-e(-) to predict the stabilityin a family of intermetallics MNiSn (M = V, Cr, Fe, and Co) crystallizingin the Co1.75Ge structure type. Site deficiencies at theM site obtained from single-crystal X-ray diffraction are understoodas attaining a stable noble gas electronic configuration. The densityfunctional theory -based structure calculation confirms that the deficientstructure is more stable than the ideal occupation available at thecrystal lattice. MnNiSn, which crystallizes in the half-Heusler crystalstructure, depicts the role of covalent radii of the constituent elementsin determining the crystal structure. Using X-ray absorption spectroscopyand X-ray photoelectron spectroscopy, the local structure of the above-mentionedcompounds was also elucidated, supporting the role of deficiency tunedvalence fluctuation to attain a 18-e(-) configurationthat eventually leads to the formation of stable compounds.

Metal deficiency tuned charge transfer in intermetallic Ni2-xSn (x =0.37-0.65) enhances selective conversion of furfural to furfuryl alcohol towards the theoretical limit - Cherevotan, Arjun; Singh, Ashutosh Kumar; Yadav, Anish; Maligal-Ganesh, Raghu V.; Raj, Jithu; Pulparambil, Anu; Goud, Devender; Vinod, Chathakudath P.; Peter, Sebastian C. (Journal of Materials Chemistry A, 2025)
Heterogeneous catalysis facilitated by intermetallic nanoparticles has recently been the subject of increased scrutiny, given the enhanced selectivity and stability they bestow on many chemical reactions compared to their monometallic components. This paper explores a series of Ni-Sn (Ni2-xSn, where x = 0.65, 0.5, 0.37) intermetallic compounds supported on a high-surface-area support, SBA-15, as catalysts for the selective hydrogenation of furfural to furfuryl alcohol. Rietveld refinements of the X-ray diffraction data show catalysts with mixed intermetallic phases that assist in the catalysis. At the same time, X-ray photoelectron spectroscopy (XPS) studies and X-ray absorption studies indicate the role played by charge transfer from Sn to Ni for the catalysis. Selectivity to the desired furfuryl alcohol in all the intermetallic samples was high (>97%), but Ni1.35Sn had a relatively lower conversion than the other intermetallic compounds.